Computation of a torsion spring stabilizer bar rigidity and fatigue resistance. (August 2019) - Geonea, I; Dumitru, N; Rosca, A; Craciunoiu, N; Racila, L; Copilusi, C
Abstract: The stabilizing bar is the suspension element that reduces the sliding of the car by stopping any kind of uneven vertical movement between the wheels to which it is connected. The stabilizer bar is a piece designed to increase stability during curves, in the case of sharp turns or maneuvers, and to enhance vehicle maneuverability. In general, sports cars are equipped with such stabilizing bars both on the front and rear. In this paper we present research on the experimental determination of the characteristic and rigidity of the torsion bar springs used in suspensions of motor vehicles. The determination of the torsion bar spring characteristic is done by two methods: analytical and experimental. The results obtained by the two methods are similar. In the second part of the paper there is discussed a test bench used for the experimental determination of fatigue resistance of the torsion bar spring. Also, angular deformations of torsion bar with resistive strain gauge transducers are monitored during fatigue applications. The results of the fatigue application are also studied by numerical simulation in the ANSYS FEA program.